Electronic Surveillance of Mobile Devices Understanding the Mobile Ecosystem and Applicable Surveillance Law - Balkovich, Edward (RAND Corporation, 2015)
Law enforcement agencies face major challenges surrounding law enforcement use of the user data collected through mobile phones and describes a prototype tool-the Mobile Information and Knowledge Ecosystem (MIKE)-that could help a wide range of stakeholders understand how information is shared within the mobile ecosystem and the legal protections that govern access to that information.